Macrophage MST1/2 Disruption Impairs Post-Infarction Cardiac Repair via LTB4. Issue 10 (10th September 2021) - Liu, Mingming; Yan, Meng; He, Jinlong; Lv, Huizhen; Chen, Zhipeng; Peng, Liyuan; Cai, Wenbin; Yao, Fang; Chen, Chen; Shi, Lei; Zhang, Kai; Zhang, Xu; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Rationale: Timely inhibition of inflammation and initiation of resolution are important to repair injured tissues. MST1/2 (mammalian STE20-like protein kinase 1/2) acts as a regulator of macrophage-associated immune responses to bacterial infections. However, the role of MST1/2 in regulating macrophage phenotype and function in myocardial infarction (MI) remains unclear. Objective: To determine the function and underlying mechanism of macrophage MST1/2 in cardiac repair post-MI. Methods and Results: Using LysMCre -mediated Mst1/2 -deficient mice, we found that MST1 deficiency exacerbated cardiac dysfunction after MI. Single-cell RNA sequencing assay indicated that the effect was attributed to a shift of macrophage subtypes from those expressing Cxcl2 and Cd163 toward Ccl2 and Ccl4 expression. Mass spectrometry identified LTB4 (leukotriene B4) as the lipid mediator that was upregulated in the absence of MST1. We found that MST1 phosphorylated 5-LOX (5-lipoxygenase) at its T218 residue, disrupting the interaction between 5-LOX and 5-LOX-activating protein, resulting in a reduction of LTB4 production. In contrast, a 5-LOX T218A variant showed no response to MST1. Moreover, treatment of peritoneal macrophages with LTB4 or medium conditioned by Mst1 -deficient macrophages resulted in high Ccl2 and Ccl4 expression and low Cxcl2 and Cd163 expression, except when the cells were co-treated with the BLT1 (LTB4 receptor 1) antagonist CP105696. Furthermore, CP105696 ameliorated cardiac dysfunction in LysMCre -mediated Mst1/2 -deficient mice and enhanced cardiac repair in wild-type mice treated with XMU-MP-1 (4-((5, 10-dimethyl-6-oxo-6, 10-dihydro-5H-pyrimido[5, 4-b]thieno[3, 2-e][1, 4]diazepin-2-yl)amino)benzenesulfonamide) after MI. Conclusions: Taken together, our results demonstrate that inhibition of MST1/2 impaired post-MI repair through activating macrophage 5-LOX–LTB4–BLT1 axis.